1975
DOI: 10.1126/science.1179211
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Formation in First and Second Generation Offspring of Nutritionally Deprived Rats

Abstract: Prolonged partial restriction of calorie intake in young rats results in reduced growth, involution of lymphoid organs, and lymphopenia. After immunization with sheep red blood cells, the number of antibody-forming cells in the spleen and serum hemolysin titers are markedly reduced. The effect is more pronounced on the primary response and on immunoglobulin G antibody-forming cells. Significant impairment of antibody formation is detectable in the first (F1) and second (F2) generation offspring of starved Fo m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(57 citation statements)
references
References 25 publications
2
54
0
1
Order By: Relevance
“…In addition, slow rates of growth in infancy-likely indicative of inadequate postnatal nutrition-are associated with reduced vaccine responsiveness and thymopoietin production in adolescence (16,23). These findings build on early research with animal models, showing that undernourished rats give birth to offspring with immune deficiencies that last into adulthood, although the offspring had unrestricted access to food (24,25).…”
Section: Ecological Variation and Developmental Plasticity In The Hummentioning
confidence: 90%
“…In addition, slow rates of growth in infancy-likely indicative of inadequate postnatal nutrition-are associated with reduced vaccine responsiveness and thymopoietin production in adolescence (16,23). These findings build on early research with animal models, showing that undernourished rats give birth to offspring with immune deficiencies that last into adulthood, although the offspring had unrestricted access to food (24,25).…”
Section: Ecological Variation and Developmental Plasticity In The Hummentioning
confidence: 90%
“…Early research with murine models documented alterations in offspring immune function following maternal nutritional deficiencies (both macro-and micronutrient) that lasted into adulthood and even the next generation, despite ad libitum feeding of both F 1 and F 2 generations (Beach et al, 1982;Chandra, 1975a). Recently, we reported that prenatal undernutrition is associated with impaired antibody responsiveness and reduced thymic hormone production in Filipino adolescents (McDade et al, 2001a,b).…”
Section: Fetal Developmentmentioning
confidence: 99%
“…These general findings have been observed in infants as well as in laboratory animals (Chandra 1975b(Chandra , 1991Moscatelli et al 1976). In animal models of intrauterine nutritional deficiency, protein-energy malnutrition as well as deprivation of selected nutrients results in reduced immune responses in the offspring (Chandra, 1975c). Briefly, the number of T lymphocytes is reduced and their response to mitogens is decreased.…”
Section: Immune Responsesmentioning
confidence: 99%